Global trends, practices, and challenges in contemporary tourism and hospitality management - Batabyal, Debasish, 1978-; Das, Dilip Kumar, 1974- (IGI Global, 2020)
"This book examines changes and issues involved in global tourism practices. It analyzes new trends in the tourism, hospitality, and transport sectors. It also explores the influence and use of technology in the tourism industry"--